English students’ subjectivity (Re)construction within the english language-related discourse of success: a narrative study (2022)
This thesis presents the design, the process, and the result of a narrative qualitative research developed from 2019 to 2021. Its main objective was to unveil a group of English language students’ subjectivity (re)construction in connection to the English-language-related discourse of success. The research problem arose from my daily interaction, as a teacher and as a researcher, with the English language students in a non-formal education institution in Bogotá. There, students perpetuated the decision of studying English following the idea of English as a synonym of success and hoping to have economic benefits from its learning. This qualitative study drew from the narrative inquiry model of Barkhuizen (2013) and consisted of the reflection, creation, and collection of four written life stories (WLS) regarding the participants’ English language learning experience. The analysis of data followed three stages: organization, reduction, and categorization. Findings revealed that students’ subjectivity (re)construction is mediated through tensions between subjectivity and subjectivation practices. Thus, participants in the study consent power execution through the naturalized English-language-related discourse of success, they take self-responsibility in the English learning process, and struggle acquiring the English Language because of a Neoliberal ideology.